Fractionated Repetitive Extracorporeal Shock Wave Therapy: A New Standard in Shock Wave Therapy?. (27th July 2015) - Kisch, Tobias; Sorg, Heiko; Forstmeier, Vinzent; Mailaender, Peter; Kraemer, Robert
Abstract : Background . ESWT has proven clinical benefit in dermatology and plastic surgery. It promotes wound healing and improves tissue regeneration, connective tissue disorders, and inflammatory skin diseases. However, a single treatment session or long intervals between sessions may reduce the therapeutic effect. The present study investigated the effects of fractionated repetitive treatment in skin microcirculation. Methods . 32 rats were randomly assigned to two groups and received either fractionated repetitive high-energy ESWT every ten minutes or placebo shock wave treatment, applied to the dorsal lower leg. Microcirculatory effects were continuously assessed by combined laser Doppler imaging and photospectrometry. Results . In experimental group, cutaneous tissue oxygen saturation was increased 1 minute after the first application and until the end of the measuring period at 80 minutes after the second treatment ( P < 0.05 ) . The third ESWT application boosted the effect to its highest extent. Cutaneous capillary blood flow showed a significant increase after the second application which was sustained for 20 minutes after the third application ( P < 0.05 ) . Placebo group showed no statistically significant differences. Conclusions . Fractionated repetitive extracorporeal shock wave therapy (frESWT) boosts and prolongs the effects on cutaneous hemodynamics. The results indicate that frESWT may provide greater benefits in the treatment of distinct soft tissue disorders compared with single-session ESWT.